Solve using the Square Root Property 0=x^2-4.75x+3

Math
0=x2-4.75x+3
Rewrite the equation as x2-4.75x+3=0.
x2-4.75x+3=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=-4.75, and c=3 into the quadratic formula and solve for x.
4.75±(-4.75)2-4⋅(1⋅3)2⋅1
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -4.75 to the power of 2.
x=4.75±22.5625-4⋅(1⋅3)2⋅1
Multiply 3 by 1.
x=4.75±22.5625-4⋅32⋅1
Multiply -4 by 3.
x=4.75±22.5625-122⋅1
Subtract 12 from 22.5625.
x=4.75±10.56252⋅1
x=4.75±10.56252⋅1
Multiply 2 by 1.
x=4.75±10.56252
x=4.75±10.56252
Simplify the expression to solve for the + portion of the ±.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -4.75 to the power of 2.
x=4.75±22.5625-4⋅(1⋅3)2⋅1
Multiply 3 by 1.
x=4.75±22.5625-4⋅32⋅1
Multiply -4 by 3.
x=4.75±22.5625-122⋅1
Subtract 12 from 22.5625.
x=4.75±10.56252⋅1
x=4.75±10.56252⋅1
Multiply 2 by 1.
x=4.75±10.56252
Change the ± to +.
x=4.75+10.56252
Add 4.75 and 10.5625.
x=82
Divide 8 by 2.
x=4
x=4
Simplify the expression to solve for the – portion of the ±.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -4.75 to the power of 2.
x=4.75±22.5625-4⋅(1⋅3)2⋅1
Multiply 3 by 1.
x=4.75±22.5625-4⋅32⋅1
Multiply -4 by 3.
x=4.75±22.5625-122⋅1
Subtract 12 from 22.5625.
x=4.75±10.56252⋅1
x=4.75±10.56252⋅1
Multiply 2 by 1.
x=4.75±10.56252
Change the ± to -.
x=4.75-10.56252
Subtract 10.5625 from 4.75.
x=1.52
Divide 1.5 by 2.
x=0.75
x=0.75
The final answer is the combination of both solutions.
x=4,0.75
Solve using the Square Root Property 0=x^2-4.75x+3

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top